Rick Gallaher's MPLS training guide : building multi-protocol label switching networks - Gallaher, Rick (Syngress Pub., 2003)
This book introduces readers to mpls concepts, installation, migration, operation, inspection, and troubleshooting. It discusses specific router and switch platforms and includes such topics as frame-mode mpls, cell-mode mpls, label distribution protocol, tag distribution protocol, label distribution protocol migration, mpls configuration, traffic engineering, mpls vpns, mpls vpn deployment models, mpls vpn routing protocol support, multi-protocol bgp, mpls vpn configurations, mpls vpn integration, and mpls vpn management. Readers will find complete ready-to-use configurations for routers Shows how to implement MPLS traffic engineering on a core network and optimize traffic Great for users studying for Cisco's Implementing Cisco MPLS exam, 640-910 and written by a Cisco internetworking expert who knows everything about MPLS. Includes coverage of Cisco Systems' newly released (October 7, 2002) Multiprotocol Label Switching (MPLS) Bandwidth Protection software package. The new architecture uses MPLS Traffic Engineering Fast Reroute and an offline application called Tunnel Builder Pro to increase resiliency at a network-wide level. Includes updated coverage of MPLS and GMPLS.